Mechanism for the recent ocean warming events on the Scotian Shelf of eastern Canada. (15th March 2018) - Brickman, D.; Hebert, D.; Wang, Z.
Abstract: In 2012, 2014, and 2015 anomalous warm events were observed in the subsurface waters in the Scotian Shelf region of eastern Canada. Monthly output from a high resolution numerical ocean model simulation of the North Atlantic ocean for the period 1990–2015 is used to investigate this phenomenon. It is found that the model shows skill in simulating the anomaly fields derived from various sources of data, and the observed warming trend over the last decade. From analysis of the model run it is found that the anomalies originate from the interaction between the Gulf Stream and the Labrador Current at the tail of the Grand Banks (south of Newfoundland). This interaction results in the creation of anomalous warm/salty (or cold/fresh) eddies that travel east-to-west along the shelfbreak. These anomalies penetrate into the Gulf of St. Lawrence, onto the Scotian Shelf, and into the Gulf of Maine via deep channels along the shelfbreak. The observed warming trend can be attributed to an increase in the frequency of creation of warm anomalies during the last decade. Strong anomalous events are commonly observed in the data and model, and thus should be considered as part of the natural variability of the coupled atmosphere-ocean system. Abstract : Highlights: Observed TS anomalies in deep waters of eastern Canadian shelf region investigated. Numerical circulation model simulation compares favorably with observations. Anomalies generated at the Tail of the Grand Banks. Interaction of Gulf Stream and Labrador Current causes anomalies. Anomalous eddies travel east-west along shelfbreak, invading shelf region.